THE ROLE OF ISLAMIC RELIGIOUS EDUCATION LEARNING IN INCREASING COGNITIVE DEVELOPMENT FOR CHILDREN MENTALLY DISABLED - Salsabila Azzahra; Salma Putri Nadipa; Khoirunnisa; Reka Andika; Rosa Triana Wulandari; Saliyya Elkayyisa Luthfia; Ulis Mayrosa; Wina Pebriani; Thifal Augista Ristyanda; Lu’lu Zahirah Ali; Nabila Amaliah; Sarvika Ananda Fitria; Beti Fitrianingsih; Clarissa Salsabila Gunawan (CV. Doki Course and Training, 2023)
This study aims to describe the results of relevant research regarding the Islamic religious learning model in cognitive development for mentally retarded children and provide solutions to these learning problems. This study uses a qualitative method with a case study approach. Methods of data collection in the form of interviews, observation, and documentation. Primary data sources were obtained through Islamic religion subject teachers at SLB B Pembina Palembang through an interview process. It is hoped that from this source data related to the learning process, learning models, and learning situations will be obtained. As for other data obtained from observations during Islamic religious learning in class IX SMPLB mental retardation and documents, namely the process of searching for theories and other data through books or journals. The results of this study state that of the various learning models applied, mentally retarded students will be able to understand the material if it is repeated continuously by the teacher for an unlimited period of time. Learning models such as reading, writing, practicing, watching, and listening to seek and prepare students in understanding the teachings of the Islamic religion. However, mental retardation has cognitive limitations that cause students to have problems in the learning process. So that there are problems with mentally retarded children at SLB B Negeri Pembina Palembang, namely, mentally retarded students easily forget and are slow in understanding and memorizing the material provided.